Lead your boss the subtle art of managing up - Baldoni, John. (New York AMACOM, 2010)
Every manager on the move wants to have influence at the top in order to get his or her ideas heard and ultimately acted upon. In Lead Your Boss, recognized leadership guru John Baldoni gives managers new as well as tried and true methods for influencing both their bosses and their peers, and giving senior leaders reasons to follow their lead. Featuring instructive stories based on real-life experiences from leaders at all levels. Lead Your Boss gives readers practical, tactical advice on becoming a key player in any organization, regardless of whether or not they have an office in the Csuite! YET.
Includes bibliographical references and index.
Keywords: Managing your boss